CCR5 is Involved in Resolution of Inflammation in Proteoglycan-Induced Arthritis - Doodes, Paul D. (2009)
OBJECTIVE: CCR5 and its ligands (CCL3, CCL4 and CCL5) may play a role in inflammatory cell recruitment into the joint. However, recently it has been reported that CCR5 on T cells and neutrophils acts as a decoy receptor for CCL3 and CCL5 to assist in resolution of inflammation. To determine whether CCR5 functions as a pro-inflammatory or anti-inflammatory mediator in arthritis, we examined the role of CCR5 in proteoglycan (PG)-induced arthritis (PGIA). METHODS: PGIA was induced by immunization of BALB/c wild type (WT) and CCR5-deficient (CCR5(−/−)) mice with human PG in adjuvant. The onset and severity were monitored overtime. Met-RANTES was used to block CCR5 in vivo. Arthritis was transferred to SCID mice with spleen cells from arthritis WT and CCR5(−/−) mice. Cytokines and chemokines were measured by ELISA. RESULT: Treatment with the CCR5 inhibitor, Met-RANTES, and CCR5(−/−) mice developed exacerbated arthritis late in the course of disease. The increase in arthritis severity in CCR5(−/−) correlated with elevated serum levels of CCL5. However, exacerbated arthritis was not intrinsic to the CCR5(−/−) lymphoid cells as arthritis transferred into SCID recipients was similar in WT and CCR5(−/−) mice. CCR5 expression in the SCID was sufficient to clear CCL5 as serum levels of CCL5 were the same in SCID recipients receiving WT or CCR5(−/−) cells. CONCLUSION: These data demonstrate that CCR5 is a key player in controlling the resolution of inflammation in experimental arthritis.